Turning optical switching properties of Mg-Y films in electrochemical process by tailoring composition. (28th March 2018) - Fu, Kai; Chen, Jun; Deng, Jifeng; Li, Shuan; Guo, Yanru; Tian, Wenhuai; Li, Xingguo
Abstract: A series of Pd capped Mg-Y binary thin films have been prepared by direct current magnetron co-sputtering and their optical switching properties combined with electrochemical potential profiles have been investigated. The maximum optical transmittance of Mg-Y/Pd thin films in the hydrogenated state, are not positively related to the Mg-Y ratio. The phase composition and grain size of the thin films have been found to greatly affect the electrochromic properties of Mg-Y thin films. As long as Mg particles is present in the thin film, the optical transmittance remains low as these metallic Mg are hard to completely hydrogenated and maintain highly reflective state in charging process. Forming intermetallic (i.e. Mg24 Y5, Mg2 Y and MgY) in pristine thin films is crucial and favorable to achieve high optical transmittance in the hydrogenated state. In these samples containing intermetallic only, the in situ generated Mg domains have very small size and are surrounded by the YH2 domain. The YH2 domains provide fast H diffusion path, sufficient hydrogen source and nucleating agents, which, together with the small Mg domain size, results in complete hydrogenation of the thin films.